2018
DOI: 10.1213/ane.0000000000002394
|View full text |Cite
|
Sign up to set email alerts
|

The Coagulation Profile of End-Stage Liver Disease and Considerations for Intraoperative Management

Abstract: The coagulopathy of end-stage liver disease results from a complex derangement in both anticoagulant and procoagulant processes. With even minor insults, cirrhotic patients experience either inappropriate bleeding or clotting, or even both simultaneously. The various phases of liver transplantation along with fluid and blood product administration may contribute to additional disturbances in coagulation. Thus, anesthetic management of patients undergoing liver transplantation to improve hemostasis and avoid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 144 publications
1
47
0
4
Order By: Relevance
“…Although INR has been a popular reference point to assess coagulopathy, systematic reviews have found it to be an incomplete indicator of coagulation status and a poor predictor of intraoperative bleeding risk . Similar to our findings, studies in cirrhotic adult liver transplant patients have found that preprocedural transfusion to a specific INR threshold did not translate to differences in periprocedural blood transfusions .…”
Section: Discussionsupporting
confidence: 80%
“…Although INR has been a popular reference point to assess coagulopathy, systematic reviews have found it to be an incomplete indicator of coagulation status and a poor predictor of intraoperative bleeding risk . Similar to our findings, studies in cirrhotic adult liver transplant patients have found that preprocedural transfusion to a specific INR threshold did not translate to differences in periprocedural blood transfusions .…”
Section: Discussionsupporting
confidence: 80%
“…22 However, this can be concerning in cardiac cases in which full heparinization is necessary, in aortic stenosis patients who have acquired von Willebrand disease and angiodysplasia, 23 and in end-stage liver disease patients who commonly have esophageal or gastric varices as well as coagulopathy. 24 Especially for aortic valvulopathy patients or aortic valve procedures, transgastric or deep transgastric TEE views are useful for assessment of aortic valve pressure gradient and valve integrity, and it is important to minimize unnecessary manipulations of the TEE probe.…”
mentioning
confidence: 99%
“…Thomas [5] and Thomas et al [33] studied safe epidural catheter removal with advanced haemostatic viscoelastic tests and found the tests not well validated in this context; there are frequent false negative (apparently normal) test results. However, a clearly abnormal TEG Âź or ROTEM Âź curve indicates deranged haemostasis, and must be taken seriously [5,34]. Factor Xa activity can be measured, and where available, can be an important help in evaluating bleeding risk from factor Xa inhibitors (Table 2b).…”
Section: Monitoring Of Haemostasis With Advanced Haemostatic Testsmentioning
confidence: 99%
“…factor deficiencies, but also imbalance between production and destruction of platelets, resulting in thrombocytopenia [73]. Reductions in both pro-and anti-coagulant factors seem to be able to balance each other, and platelet dysfunction is compensated, at least in part, by a concomitant increase in the von Willebrand factor [34,72]. In patients with liver cirrhosis, the risk of systemic thromboembolism can be greater than the risk of bleeding [34].…”
Section: Estimate Glomerular Filtration Rate (Egfr) In Elderly Patienmentioning
confidence: 99%